Sustainability of protocolized handover of pediatric cardiac surgery patients to the intensive care unit. Issue 5 (21st March 2016) - Chenault, Kristin; Moga, Michael‐Alice; Shin, Minah; Petersen, Emily; Backer, Carl; De Oliveira, Gildasio S.; Suresh, Santhanam
Summary: Background: Transfer of patient care among clinicians (handovers) is a common source of medical errors. While the immediate efficacy of these initiatives is well documented, sustainability of practice changes that results in better processes of care is largely understudied. Aims: The objective of the current investigation was to evaluate the sustainability of a protocolized handover process in pediatric patients from the operating room after cardiac surgery to the intensive care unit. Methods: This was a prospective study with direct observation assessment of handover performance conducted in the cardiac ICU (CICU) of a free‐standing, tertiary care children's hospital in the United States. Patient transitions from the operating room to the CICU, including the verbal handoff, were directly observed by a single independent observer in all phases of the study. A checklist of key elements identified errors classified as: 1) technical, 2) information omissions, and 3) realized errors. Total number of errors was compared across the different times of the study (preintervention, postintervention, and the current sustainability phase). Results: A total of 119 handovers were studied: 41 preintervention, 38 postintervention, and 40 in the current sustainability phase. The median [Interquartile range (IQR)] number of technical errors was significantly reduced in the sustainability phase compared to the preintervention and postintervention phase, 2 (1–3), 6 (5–7), and 2.5 (2–4), respectively P = 0.0001. Similarly, the median (IQR) number of verbal information omissions was also significantly reduced in the sustainability phase compared to the preintervention and postintervention phases, 1 (1–1), 4 (3–5) and 2 (1–3), respectively. Conclusions: We demonstrate sustainability of an improved handover process using a checklist in children being transferred to the intensive care unit after cardiac surgery. Standardized handover processes can be a sustainable strategy to improve patient safety after pediatric cardiac surgery. Abstract :